The Value of Sentinel Lymph Node Mapping for the Staging of Node-Negative Colon Cancer: Propensity Score and Mediation Analyses. Issue 3 (26th September 2021) - Weixler, Benjamin; Ramser, Michaela; Warschkow, Rene; Viehl, Carsten T.; Vaughan-Shaw, Peter G.; Zettl, Andreas; Kettelhack, Christoph; Zuber, Markus
Abstract : Objectives: Mediation analysis to assess the protective impact of sentinel lymph node (SLN) mapping on prognosis and survival of patients with colon cancer through a more precise evaluation of the lymph node (LN) status. Background: Up to 20% of patients with node-negative colon cancer develop disease recurrence. Conventional histopathological LN examination may be limited in describing the real metastatic burden of LN. Methods: Data of 312 patients with stage I & II colon cancer was collected prospectively. Patients were either staged using intraoperative SLN mapping with multilevel sectioning and immunohistochemical staining of the SLN or conventional techniques. The value of the SLN mapping for the detection of truly node-negative patients was assessed using Cox regression and mediation analysis. Results: SLN mapping was performed in 143 patients. Disease recurrence was observed in 13 (9.1%) patients staged with SLN mapping and in 27 (16%) staged conventionally. Five-year overall survival (OS) rate was 82.7% (95% confidence interval [CI], 76.5–89.4%) with SLN mapping compared with 65.8% (95% CI, 58.8–73.7%). Five-year cancer-specific survival (CSS) was 95.1% (95% CI, 91.3–99.0%) with SLN mapping compared with 92.5% (95% CI, 88.0–97.2%). Node-negative staging with SLN mapping was associated with significantly better OS (hazard ratio [HR], 0.64; 95% CI, 0.56–0.72; P < 0.001) and CSS (HR, 0.49; 95% CI, 0.39–0.61; P < 0.001) in multivariate analysis. Mediation analysis confirmed a direct protective effect of SLN mapping on OS (HR, 0.78; 95% CI, 0.52–0.96; P < 0.01) and disease-free survival (DFS) (HR, 0.75; 95% CI, 0.48–0.89; P < 0.01). Conclusions: Staging performed by SLN mapping with multilevel sectioning provides more accurate results than conventional staging. The observed clinically relevant and statistically significant benefit in OS and DFS is explained by a more accurate detection of positive LN by SLN mapping. Abstract : Mini-abstract: Sentinel lymph node mapping with multilevel sectioning and immunohistochemical staining provides more accurate staging results in patients with colon cancer. It is associated with a significant better survival outcome, while mediation analysis confirmed a direct protective effect on overall survival and disease-free survival.